The Changing Face of Cystic Fibrosis and Its Implications for Screening - Lutz Naehrlich (MDPI AG, 2020)
Early diagnosis, multidisciplinary care, and optimized and preventive treatments have changed the face of cystic fibrosis. Life expectancy has been expanded in the last decades. Formerly a pediatric disease, cystic fibrosis has reached adulthood. Mutation-specific treatments will expand treatment options and give hope for further improvement of quality of life and life expectancy. Newborn screening for CF fits perfectly into these care structures and offers the possibility of preventive treatment even before symptoms occur. Especially in countries without screening, newborn screening will fulfill that promise only with increased awareness and new care structures.